2017
DOI: 10.15406/ipcb.2017.02.00013
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Intrauterine Foetal Demise: a Retrospective Study in a Tertiary Care Centre in India

Abstract: Objective: To determine the incidence and possible causes of Intrauterine Foetal Demise (IUFD), and to determine preventive measures. Methods:Retrospective observational study was done from Jan 2015 to Dec 2015 at the tertiary care referral hospital in Bangalore, India. Inclusion criteria were IUFD at or above 24weeksof gestation. The parameters analysed were maternal age, parity, probable causes for IUFD, booked or unbooked cases, mode of delivery, maternal complications, and placental histopathology. Data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 7 publications
6
16
1
Order By: Relevance
“…It has been found that about 44% of placental abruption is associated with maternal hypertension [ 20 ]. An Indian study found that pre-eclampsia and its consequences (abruption and eclampsia) accounted for 48.1% of all causes of stillbirths [ 15 ], which is greater than what we reported in the present study (37.6%). Our lower rate contradicts the fact that the hypertension rate is more prevalent among African men and women, which can be explained by the study nature and sample size variation.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…It has been found that about 44% of placental abruption is associated with maternal hypertension [ 20 ]. An Indian study found that pre-eclampsia and its consequences (abruption and eclampsia) accounted for 48.1% of all causes of stillbirths [ 15 ], which is greater than what we reported in the present study (37.6%). Our lower rate contradicts the fact that the hypertension rate is more prevalent among African men and women, which can be explained by the study nature and sample size variation.…”
Section: Discussioncontrasting
confidence: 85%
“…Unexplained causes remain the leading cause of stillbirths, and it accounts for 25%-50% of all-cause [ 15 ]. In the present study, 20% of cases had no identifiable causes, which is consistent with the later study.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the patients (60.6%) belonged to the age group of 20 -30 years which is similar to the studies [5] [6] [7].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, incidence of stillbirth or IUFD was 27.76/1000 live birth. Bhatia T et al [5], Sharma S et al [6] and Kanavi J et al [7], in their study showed hospital incidence of stillbirth or IUFD 23.46/1000 live birth, 36/1000 live birth and 39/1000 live birth respectively. Which were higher rate than our study, in our study incidence was lower, as most of the delivery that is about 53% of delivery in our country occur at home.…”
Section: Discussionmentioning
confidence: 91%
“…However it is lower than the findings of the study by Kanavi et al which showed 10% of patients with IUFD had history of one previous IUFD and 1.3% had history of two previous IUFDs. 19 The study of BPKIHS done in 2014 identified hypertension as the most common maternal comorbidity in patients with IUFD. Other risk factors contributing to IUFD included antepartum hemorrhage, postdated pregnancy, Intrauterine growth restriction (IUGR), and sepsis.…”
Section: Discussionmentioning
confidence: 99%